Framework of Multi-Theoretical Mechanisms in Financial Distress: The Interaction Between Financial Pressure and Liquidity Failure - Mutia Prawitasari; Trias Andati; Tony Irawan (Indonesian Journal of Accounting, Risk and Governance, 2026)
Background: Increasing leverage and economic uncertainty heighten the risk of financial distress; however, the relationship between capital structure and distress remains inadequately explained by approaches that focus on individual determinants.Objective: This study aims to develop an integrative multi-theoretical framework to explain financial distress as a causal process involving the interaction between financial pressure and liquidity capacity using a qualitative literature-based approach.Method: This study adopts a qualitative literature-based approach by integrating trade-off theory, pecking order theory, and market timing theory, along with supporting theories such as agency theory and asymmetric information. Findings: The results indicate that capital structure outcome generates financial pressure, placing firms in a pre-distress state. However, financial distress does not arise directly from leverage; rather, it occurs when financial pressure is not offset by sufficient liquidity capacity. Within this framework, working capital management functions as a corrective mechanism that determines whether financial pressure can be absorbed or escalates into distress through liquidity failure.Conclusion: This study positions financial distress as an outcome of the interaction between financial pressure and liquidity capacity within a layered causal system, and identifies two implicit evolutionary paths: intervention through corrective mechanisms or progression toward a terminal pathway.Originality: This study contributes theoretically by shifting the perspective from direct relationships toward a mechanism-based explanation, and by positioning working capital management as a key mechanism in the transformation of financial pressure into financial distress. Keywords:capital structure, financial distress, working capital management, corporate finance